The Evolving Role of Fiscal Policy in Centrally Planned Economies Under Reform : The Case of China. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
Market-oriented economic reforms in centrally planned economies have altered the functions and objectives of key policy instruments, particularly in the case of fiscal policy. As a result of reform, economic management requires the use of 'indirect' levers to regulate the behavior of increasingly autonomous economic agents. In this respect, fiscal policy becomes central and its macroeconomic role is enhanced. This paper studies the recent Chinese experience, reviewing fiscal developments and analyzing the effectiveness and appropriateness of available fiscal instruments in performing their newly enhanced macroeconomic role.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet